2008
DOI: 10.1002/jat.1388
|View full text |Cite
|
Sign up to set email alerts
|

Butyl benzyl phthalate: effects on immune responses to ovalbumin in mice

Abstract: During recent decades the prevalence of IgE-mediated (atopic) allergic diseases in Western Europe and the USA has been increasing dramatically. It has been suggested that one possible cause is the presence in the environment of chemicals that may act as adjuvants, enhancing immune and allergic responses. Certain commonly used phthalate plasticizers such as butyl benzyl phthalate (BBP) have been implicated in this way. In the current experiments, the impact of BBP, applied by a physiologically relevant exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Those exposed to high levels had an attenuated immune response, whereas those exposed at low levels had mucosal inflammation and nonsensitized individuals had no response (Deutschle et al 2008). In murine models, BBzP enhanced anti-ovalbumin responses at high doses, but not at the lower doses potentially more consistent with human exposures (Dearman et al 2009). Few studies have evaluated whether BBzP, or its metabolite MBzP, have independent effects on immune responses at levels relevant to human exposure.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Those exposed to high levels had an attenuated immune response, whereas those exposed at low levels had mucosal inflammation and nonsensitized individuals had no response (Deutschle et al 2008). In murine models, BBzP enhanced anti-ovalbumin responses at high doses, but not at the lower doses potentially more consistent with human exposures (Dearman et al 2009). Few studies have evaluated whether BBzP, or its metabolite MBzP, have independent effects on immune responses at levels relevant to human exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have measured phthalate levels in urine or dust, although earlier studies suggested a role for phthalates due to the presence of plastic materials in the home (Jaakkola and Knight 2008; Larsson et al 2007), exposure to PVC plastics in an occupational setting (Jaakkola and Knight 2008) or use of synthetic bedding (Ponsonby et al 2003). As the evidence for a potential role for phthalates in respiratory and allergic outcomes has increased, there is greater interest in HMW phthalates such as DEHP and BBzP, with evidence both from human and animal studies (Dearman et al 2009; Deutschle et al 2008; Jaakkola and Knight 2008; Koike et al 2009; Larsen et al 2007; Nishioka et al 2012). These HMW phthalates alter immune responses in animal and in vitro models (Koike et al 2009; Larsen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…What is so astounding is that in the Taiwanese households investigated, only about 44% of dust samples collected from surfaces above the floor reached the lowest level of calibration curves, at 2 μg/g dust, and yet the significant association was still present despite the relatively low BBzP levels measured. A previous study in animals had shown the modest adjuvant effect of BBzP exposure only at a high dose of 100 mg, which was not normally encountered in the residential environment (Dearman et al., 2009). Other in vivo studies (Butala et al., 2004; Larsen et al., 2003) also did not find any associations between BBzP exposures and their health outcomes of interest.…”
Section: Discussionmentioning
confidence: 98%
“…Very recently, BPA was shown to negatively alter immune function over the life course in addition to posing a threat to endocrine and reproduction function (Clayton et al, 2010). The exposure to PAEs had been shown to be associated with increased risk of development of allergies and asthma (Dearman et al, 2009;Kimber and Dearman, 2010).…”
Section: And This Investigation Paes (Dehp/mehp and Dbp/bbp/mbp)mentioning
confidence: 99%